2016
DOI: 10.1097/iae.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Retinal Pigment Epithelium Phenotypes in the Transition to Geographic Atrophy in Age-Related Macular Degeneration

Abstract: Purpose To inform the interpretation of clinical optical coherence tomography and fundus autofluorescence?imaging in geographic atrophy (GA) of age-related macular degeneration (AMD) by determining the distribution of retinal pigment epithelium (RPE) phenotypes in the transition from health to atrophy (GA) in donor eyes. Method In RPE-Bruch’s membrane flat mounts of 2 GA eyes the terminations of organized RPE cytoskeleton and autofluorescent material were compared. In high-resolution histological sections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(148 citation statements)
references
References 101 publications
2
137
1
8
Order By: Relevance
“…Using high-resolution histology, we recently developed a system of RPE morphologic phenotypes and determined that many are visible by SDOCT 28, 29 . In eyes with GA 30 , we found that the RPE layer thickens near the border of atrophy, due to a progressive dysmorphia that also helps explain variable FAF at the margin of atrophy 31 . Here we use these same methods to investigate RPE morphology and thickness in the transition to atrophy in eyes with nvAMD.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Using high-resolution histology, we recently developed a system of RPE morphologic phenotypes and determined that many are visible by SDOCT 28, 29 . In eyes with GA 30 , we found that the RPE layer thickens near the border of atrophy, due to a progressive dysmorphia that also helps explain variable FAF at the margin of atrophy 31 . Here we use these same methods to investigate RPE morphology and thickness in the transition to atrophy in eyes with nvAMD.…”
Section: Introductionmentioning
confidence: 75%
“…The border of atrophy was defined as the descent of the external limiting membrane (ELM) towards Bruch’s membrane. 30 As described 30, 39 , the descent of the ELM is comprised of reactive Müller cell processes extending outward to approach Bruch’s membrane in areas of photoreceptor loss. An ELM descent was analyzed if it was at least 500 µm from the termination of subretinal fibrovascular scar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eyes with geographic atrophy exhibit features suggestive of motile non-epithelioid RPE, as revealed by AO-assisted IR imaging. 50 Recent imaging-histology correlations have demonstrated cells with a full complement of reflective RPE organelles within the subretinal space and retina, 46,51,52 consistent with anterior migration. Thus the range of RPE cellular activities observable in vivo has expanded in step with new visualization technologies.…”
Section: Discussionmentioning
confidence: 98%